2022
DOI: 10.3390/healthcare10020357
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Levels among Polish and Turkish Dentists during the COVID-19 Pandemic

Abstract: Working conditions, work-related stressors and high risk of infection, as well as the fear of contagion and spreading the disease to family members, may have influenced dentists’ mental health during the COVID-19 pandemic. The aim of this study was to evaluate the anxiety levels among Polish and Turkish dentists during the COVID-19 pandemic and to investigate any relevant predictors. The study was an anonymous online questionnaire-based cross-sectional study that was conducted among dentists from two countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…During the COVID-19 pandemic, dentists worldwide experienced a period of uncertainty and insecurities, putting them at increased risk of mental health problems [ 6 , 12 , 14 , 15 , 16 , 18 , 27 , 29 , 30 , 39 , 40 , 41 ]. The present study demonstrated the levels of stress and anxiety in dentists working in the state of São Paulo during the SARS-CoV-2 viral outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, dentists worldwide experienced a period of uncertainty and insecurities, putting them at increased risk of mental health problems [ 6 , 12 , 14 , 15 , 16 , 18 , 27 , 29 , 30 , 39 , 40 , 41 ]. The present study demonstrated the levels of stress and anxiety in dentists working in the state of São Paulo during the SARS-CoV-2 viral outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when anxiety and fear regarding COVID-19 were evaluated among dentists from 30 different countries (Saudi Arabia, Pakistan, India, the United Arab Emirates, China, Italy, the United Kingdom, Australia, Malaysia, the United States of America, Ireland, Israel, New Zealand, South Africa, Turkey, Germany, Kuwait, Canada, Hungary, France, Poland, Bulgaria, the Republic of the Congo, Mexico, Romania, Egypt, Switzerland, Demark, and Bahrain), it was observed that more than 72% of professionals felt an increase in the fear of close contact with patients in clinical practice, which led to increased stress and 66% of dentists reporting a desire to leave the profession [ 13 ]. Moreover, additional studies have reported an increase in the number of professionals reporting feeling fearful and seeking counseling [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived wellness survey (PWS) is a valid scale for researching and evaluating interventions in the field of perceived health, with good reliability and validity (14,15). The PWS contains 36 items which included six dimensions: physical (1,7,13,19,25,31), emotional (2,8,14,20,26,32), social (3,9,15,21,27,33), psychological (4,10,16,22,28,34), spiritual (5,11,17,23,29,35), and intellectual (6,12,18,24,30,36) which were selected based on the strength of theoretical support and the quality of empirical evidence supporting each. The PWS assesses the perceived health of individuals and their physical, mental, and spiritual states and the social health they exhibit through relationships with others.…”
Section: Perceived Wellness Surveymentioning
confidence: 99%
“…The global outbreak of COVID-19, individual fear of infectious disease, quarantine policies for infected and close contact people, the global economic recession, and unemployment have negatively affected many people’s mental health ( 3 ). Many reports show that the stress caused by COVID-19 has had a range of adverse effects on their health, such as insomnia, anxiety, depression, and the exacerbation of chronic diseases ( 4 ). Furthermore, with the increasing number of cases, medical workers suffered from great psychological and work pressure and faced a high risk of infection during the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…13 Although dentists do take extra personal protective measures while performing dental procedures, studies show that 16-24% of dentists working in Turkey have been infected with SARS-CoV-2. [14][15][16] Due to the cross-contamination caused by aerosols, dental professionals are anxious about being infected and transmitting the infection to their families and friends, which may affect their behavior and make them experience a sense of fear and anxiety. 17 Research has shown that 2.6% of dentists, 18 5.1% of healthcare professionals 19 and 3.5% of medical students 20 received psychological support during the pandemic.…”
Section: Introductionmentioning
confidence: 99%